국내 수학교육 연구의 동향 분석 -1963년부터 2019년까지 게재된 국내 수학교육 학술지 논문을 중심으로 - 방정숙(JeongSuk Pang); 조선미(SeonMi Cho); 김경훈(KyeongHun Kim); 이유진(Yu Jin Lee); 김윤영(YoonYoung Kim)외 5명 (Suhak gyoyukak yeon-gu (Online), 2019)
국내 수학교육 연구는 1960년대 이후 현재까지 주목할 만한 양적인 성장과 더불어 질적인 성장을 이루었다. 이러한 시점에서 우리나라에서 수학교육 저널이 처음 발간된 1963년부터 현재까지 50년 남짓 7개의 국내 전문 학술지에 게재된 논문을 분석하여 그간의 연구 성과를 종합적으로 검토하였다. 구체적으로 총 4559편의 논문을 연구시기, 연구주제, 연구방법, 연구대상 측면에서 면밀히 분석하였다. 그 결과, 국내 수학교육 연구는 1990년대부터 급격하게 증가하기 시작하였으며 현재까지 꾸준히 많은 연구가 진행되고 있다. 연구주제 측면에서 국내 수학교육 연구는 수업 및 지도 방안, 학습자의 인지적ㆍ정의적 특성 및 능력 등의 연구가 가장 많이 연구된 반면에 교육공학 및 교구, 평가에 대한 연구는 별반 연구되지 않았다. 연구방법의 측면에서 국내 수학교육 연구는 분석연구, 사례연구, 조사연구의 비중이 높은 편이었고, 연구대상의 측면에서는 초등학생, 중등학생을 대상으로 한 연구의 비중이 높은 편이었다. 이러한 결과를 토대로 국내 수학교육 연구의 향후 발전 방향과 후속 연구에 대해 시사점을 논의하였다. An analysis of domestic research in the field of mathematics education over the past decades shows that there has been a steady growth in this field of research for both qualitative and quantitative analyses. The main aim of this study is to analyze the trends of domestic research on mathematics education in terms of the publication periods, research topics, research methods, and target research population. In this respect, a total of 4559 research articles dealing with mathematics education in seven professional journals published from 1963 to the present were analyzed. The results of this study showed that the number of articles on mathematics education has been rapidly increased since the 1990s. With respect to the topics, studies on instruction and, learners’ abilities or characteristics have been the most frequent. However, there has been lack of research on assessment and technology, or manipulative materials. With respect to the research methods, analytic study of literature, case study, and survey have been most frequently applied methods. With respect to the target research population, the main participants were either elementary or secondary school students. In conclusion, this paper identifies important implications for future research directions on mathematics education in Korea. KCI Citation Count: 0